2013
DOI: 10.1021/la403418h
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Segregation in Polymer Blends Driven by Acid–Base Interactions

Abstract: Infrared-visible sum frequency generation spectroscopy (SFG) was used to measure the interfacial concentrations of poly(methyl methacrylate) (PMMA)/polystyrene (PS) blends next to a sapphire substrate. The acid-base interactions of carbonyl groups of PMMA with the hydroxyl groups on the sapphire drive the interfacial segregation of PMMA next to the sapphire substrate. Using the shift of sapphire surface OH peaks, we have determined the difference in interfacial energy between the PMMA/sapphire and the PS/sapph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 30 publications
0
46
0
Order By: Relevance
“…For simplicity, this model assumes 100% dissociation of CTAB head groups, although it has been reported that the dissociation can be as low as 21% ( 34 ). The surface density of −OH groups on sapphire surface ( 35 ), molecular dimensions for CTAB ( 11 , 36 ), water ( 37 ), and PETS ( 38 , 39 ) were estimated on the basis of published literature. The orthogonal packing represented is consistent with the area per molecule based on the interfacial energy measurement, 52 Å 2 per molecule, which is similar to the theoretical area calculated for orthogonal packing (text S2).…”
Section: Resultsmentioning
confidence: 99%
“…For simplicity, this model assumes 100% dissociation of CTAB head groups, although it has been reported that the dissociation can be as low as 21% ( 34 ). The surface density of −OH groups on sapphire surface ( 35 ), molecular dimensions for CTAB ( 11 , 36 ), water ( 37 ), and PETS ( 38 , 39 ) were estimated on the basis of published literature. The orthogonal packing represented is consistent with the area per molecule based on the interfacial energy measurement, 52 Å 2 per molecule, which is similar to the theoretical area calculated for orthogonal packing (text S2).…”
Section: Resultsmentioning
confidence: 99%
“… 57 For example, in the previously reported study, the ester groups in poly(methyl methacrylate) showed stronger interaction (O–H peak is shifted to 3580 cm –1 compared to free O–H peak at 3720 cm –1 ) than functional groups in polystyrene (3645 cm –1 ) when in contact with a sapphire substrate. 58 Similarly, since the interfacial adhesion of the deprotected elastomer is higher, we speculated that there might be a larger shift for the deprotected elastomer as compared to protected elastomer, which would indicate a stronger bond between the hydroxyl groups of catechol and the sapphire.…”
Section: Results and Discussionmentioning
confidence: 95%
“… 57 A sapphire surface typically has around nine O–H groups per nm 2 , and hence macroscopically, this interaction can contribute to a maximum interfacial threshold energy ( G 0 ) of 0.10 J/m 2 for both elastomers assuming all the surface O–H groups are participating equally in this interaction. 54 , 58 …”
Section: Results and Discussionmentioning
confidence: 99%
“…36,37 By multiplying the number density of sapphire OH (n) and the enthalpy of PDMS-sapphire interactions (∆H, calculated using the frequency shift via the Badger-Bauer equation), i.e., n*∆H, we calculate the PDMS-sapphire work of adhesion to be 70±12 mJ/m 2 . 29,36,39,40,60 The contribution of acid-base interactions to the work of adhesion between PDMS and silica gel has been previously determined by measuring the heat of adsorption using calorimetry (16 mJ/m 2 ). 58 The W a calculated by adding the loading W a (52 mJ/m 2 , dominated by vdW interactions) and the acid-base W a (16 mJ/m 2 ) is similar to the value estimated from our spectroscopy experiments (70±12 mJ/m 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38] Further, this concept successfully predicted the preferential surface segregation of strongly interacting component from binary liquid mixtures, polymer blends, and polymer solutions, consistent with experimental and simulation results. [39][40][41][42] The differences in the frequency shift of sapphire OH peak in contact with another media with or without graphene layer could provide direct evidence of graphene's transparency towards vdW and polar interactions.…”
Section: Introductionmentioning
confidence: 99%